PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM-ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR GEOGRAFI - Juliani, Dina; Margiati, K.Y; Christanto, Hari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to analize the effect of applying cooperative learning student team-achievement division typeto hydrosphere for learning outcomes of the X grade students in SMA Mujahidin Pontianak. The research method that  used is experimental research which is quasy experimental with nonequivalent control group design. The populasion of this research is the whole of the X grade students in SMA Mujahidin Pontianakwith total 97 students. The sample of this research are class  X IPS 2 (control) and X IPS 3 (experiment). The average learning outcomes of post-test class experiment is 77 and class control is 68 gained  is 4,089 and   α = 5% is 1,999. So,  (4,089) > (1,999).Then , Ha is accepted. It can be conclude that there is the effect of applying cooperative learning type student team-achievement division to the learning outcome of X grade students in SMA Mujahidin Pontianak. Therefore, the effect size is 0,91(high criteria). It means that learning by applying cooperative learning type student team-achievement division to hydrosphere gives high effect to the X grade students in SMA MujahidinPontianak  learning outcomes.Keywords: Student Team-Achievement Division, Learning Outcom